Supporting social justice through equity-based actions for a sustainable future in animal genetics (at the 39th International Society for Animal Genetics Conference) - Paez, S.; Mapholi, N.O.; Nesengani, L.T.; Lamont, S.J.; Aggrey, S.E.; Hanotte, Olivier H.; Bottema, C.D.K.; Gill, C.A. (Wiley, 2025)
The 39th International Society for Animal Genetics conference (ISAG) was held for the first time in Africa under the theme ‘Animal genetics for a sustainable future’ in 2023. The conference convened scientists, policy makers, industry professionals, and students from interdisciplinary fields to share and discuss the latest developments in the space of animal genetics. Since its inception as a society, ISAG has sought to provide a platform advocating for a just and equitable future in animal genetics. At the 39th ISAG conference, this commitment towards furthering inclusion in animal genetic science was progressed with two new offerings to attendees. The first session guided discussions on the political, ethical, legal, socioeconomic, and cultural dynamics that present barriers to participating in and benefitting from the genomic and genetic science fraternity. This session also included principles of social justice, specifically equity, diversity, and inclusion, towards enacting fairness in an unfair world, and focused on constraints related to sustainability in animal genetics. The second session used the important tradition of storytelling to transfer knowledge and wisdom from experienced scientists to upcoming researchers. Experienced scientists shared lived experiences on educational and career paths, challenges, and opportunities, providing networking and opportunities for further mentoring. Here, we report on these equity-based actions and their relevance to address the urgent continent-specific and global disparities in animal genetics to move towards a sustainable future.